Prevalencia de sarcosporidiosis por inspeccion en bovinos sacrificados en el camal municipal de Balsas - Piedra Gonzales, Jorge Vicente (2007)
The present investigation was carried out in the Municipal Camal of the Balsas Canton on the El Oro in the months of August to September of the 2007, being inspected a bovine total of 250 of which 41 were positive and 209 negatives giving us a prevalencia of 16,4%. The biggest prevalencia according to the age was given in the animals older than two years 18,18%, and smaller than two years 12,16%. As for the race the susceptible one was the Holstein with 32,89% continued by Mestizo 12,82% and Brahmin 8.8%. According to the sex the females have the highest prevalencia with 19,51%, while the males 14,88% of susceptibility. The Zamora Chinchipe province had a prevalencia of 39,65% followed by Loja province 38,09%, Pichincha 7,69% and the smallest percentage The El Oro province 5,69%. As for the cantons of more parasitosis it is Palandra, Chaguarpamba, Santo Domingo and with smaller frequency Balsas. And the place with more parasitosis is Santa Elena.